POLITICAL BRANDING SAMSUL ARIFIN DALAM PEMILIHAN KEPALA DESA TAMBAKBOYO KECAMATAN TAWANGSARI KABUPATEN SUKOHARJO TAHUN 2018 - Muhammad Iqbal Firmansyah; Dwi Windyastuti Budi Hendrarti (Universitas Airlangga, 2020)
This research describes about political branding and political branding communication strategies of Samsul Arifin in Headman election of Tambakboyo in 2018. Samsul Arifin is youngest headman candidate in Sukoharjo who won the headman election in 2018 against incumbent who had two periods of leadership. This study uses descriptive qualitative method with in-depth interviews data collection techniques with Samsul Arifin and the Samsul team coordinator then it was analyzed by using Lorann Downer’s theory of political branding strategies. The results are Samsul has brand himself as a young man who will build the village government that has been damaged in the previous period. Samsul delivered his political brand by collaborating with the RT in appointing Samsul as a headman candidate, the youths are conditioning their parents, socializing in the RT forum, asking for blessing to the residents of hamlet (sub village) I, speech during registration of candidate, forming a Samsul’s wings team, anticipating of vote buying which usually do in early morning, using banner and making t- shirts for voters who are in Samsul’s side. The political brand must be implemented according to the concept, so it is not damaging candidate’s brand.